Handbook of research on inventive bioremediation techniques - Bhakta, Jatindra Nath (Advances in environmental engineering and green technologies (AEEGT) book series, 2017)
This book presents and draws a novel picture in current advancements of theoretical and practical frameworks of application from latest empirical research findings considering various aspects of bioremediation. It also address topics such as bioremediation, genomics, proteomics, remediation strategies of various hazardous pollutants, microbial remediation, phytoremediation, bioleaching, biosorption.